The great reflation : how investors can profit from the new world of money - Boeckh, J. Anthony (Hoboken, N.J. : John Wiley & Sons, 2010)
This book provides investors with knowledge insights, background and tools for building and protecting wealth. It serves as a guide by providing tools to navigate tommorrow's rapidly evolving financial landscape. It contains informations that helps understand the new world of money and how it will pay out for investments and business.
Part I: Finacial instability -- The age of inflation -- The debt super cycle, illiquidity, and the crash of 2008-2009 -- The long wave in the economy -- Government deficits and the great reflation -- Money and the great reflation -- Financial manias and bubbles. Part II: The markets: preparing for the new investment environment -- Asset allocation: investing in a turbulent world -- The stock market -- Interest rates and the bond market -- The U.S. dollar -- Gold -- Commodities -- Real estate -- Part III: The future: is a return to lasting stability possible? -- Declining America: will it recover? -- Politics and policies in the long wave trough.
Includes bibliographical references (p. 293-301) and index.
opc 29/04/13
Loans
Keywords: Investments -- United States -- History; Finance -- United States -- History; Business cycles -- United States -- History; Financial crises -- United States -- History